2023
DOI: 10.1136/bmjopen-2022-069390
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the prevalence of thyroid nodules in adults in Northeast China: a cross-sectional population-based study

Yudie Yan,
Junhe Dong,
Shufeng Li
et al.

Abstract: ObjectivesThis study examined the association between anthropometric measurements, lifestyle factors and the prevalence of thyroid nodules among adults in Northeast China.DesignWe employed a cross-sectional approach involving a questionnaire survey, which focused on participants’ living habits, and a physical examination that included anthropometry and ultrasound imaging.SettingThe data were procured during multiple trips by medical teams from the first hospital of China Medical University to towns in Northeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A study conducted in the Japanese military population from 1990 to 2012 found a significant increase in the prevalence of thyroid nodules in young men when compared to middle-aged men, but not vice versa. A thyroid nodule in some cases can transform into malignancy although the frequency is relatively low at around 5%-10% (Yan et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the Japanese military population from 1990 to 2012 found a significant increase in the prevalence of thyroid nodules in young men when compared to middle-aged men, but not vice versa. A thyroid nodule in some cases can transform into malignancy although the frequency is relatively low at around 5%-10% (Yan et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%